2020
DOI: 10.3390/ma13204649
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Eco-Friendly Betanin Hybrid Materials Based on Palygorskite and Halloysite

Abstract: Eco-friendly betanin/clay minerals hybrid materials with good stability were synthesized by combining with adsorption, grinding, and heating treatment using natural betanin extracted from beetroot and natural 2:1 type palygorskite or 1:1 type halloysite. After incorporation of clay minerals, the thermal stability and solvent resistance of natural betanin were obviously enhanced. Due to the difference in the structure of palygorskite and halloysite, betanin was mainly adsorbed on the outer surface of palygorski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 68 publications
(109 reference statements)
0
4
0
Order By: Relevance
“…Stable pigments were obtained by combining anthocyanin with different clay minerals [45][46][47][99][100][101][102][103]. Furthermore, the pigments obtained had reversibility properties under acidic and basic conditions.…”
Section: Strategies For Stability Of Anthocyanins Using Clays and Cla...mentioning
confidence: 99%
“…Stable pigments were obtained by combining anthocyanin with different clay minerals [45][46][47][99][100][101][102][103]. Furthermore, the pigments obtained had reversibility properties under acidic and basic conditions.…”
Section: Strategies For Stability Of Anthocyanins Using Clays and Cla...mentioning
confidence: 99%
“…The Fourier transform infrared (FTIR) spectra, transmitting electron microscopy (TEM), powder X-ray diffraction (XRD) analysis, Zeta potentials, Field emission transmission electron microscopy (TEM), and X-ray photoelectron spectroscopy (XPS) of the samples were obtained according to our previously reported methods ( Li et al, 2020a ). The elemental analysis of all samples was determined by Elementar analyzers varioEL cube (Elementar Analysen systeme GmbH, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…As early as 1966, van Olphen confirmed, as Dogenech-Carbo et al later demonstrated, that Pal was more beneficial than other clay minerals in stabilizing the natural indigo molecules ( Van Olphen, 1966 ; Domenech-Carbo et al, 2013 ). To date, in order to stabilize natural pigments, such as betanin, flavylium cations and anthocyanin, and expand their application fields, Pal-based hybrid pigments have been developed due to the excellent performances, such as superior stability, fluorescence and acid/base reversible allochroic behavior ( Silva et al, 2018 ; Li et al, 2019a ; Li et al, 2020a ). In this context, Pal is an attractive supporting matrix that can be employed as an inorganic carrier to stabilize Cur molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Glotov and Lvov, for example, reported a self-assembly strategy via centhyltrimethyl ammonium bromide onto negative HNTs surface, to obtain MCM-41/HNTs material with enhanced thermal and mechanical stability [ 12 ]. An example of chemical mixture between two clay was reported by Mu and Wang [ 13 ]. In this case palygorskite and halloysite were combined to improve betain adsortpion.…”
Section: Introductionmentioning
confidence: 99%